Evaluation of haematological responses of Clarias gariepinus (Burchell 1822) to ammonia and nitrite levels in some selected fish farms in ibadan, Nigeria (2005)
This study evaluated the levels of ammonia and nitrite in Clarias gariepinus in some selected fish farms in Ibadan. Twelve active fish farms were selected on the basis of their cultural practices and environments: extensive 4 each from semi-intensive and intensive systems. Ammonia and nitrite levels and their sources to the farms were studied. Blood samples of randomly selected 20 C gariepinus were collected in each of these farms and evaluated for primary and secondary stress indicators. The mean PCV (37.1 ±7.3%), WBC (3.4 ± 3.21 103/mm3) of fish samples from farms with semi intensive system were the highest (P<0.05) when compared with the other culture systems. The mean values of plasma cortisol (70.29 ± 8.9ng/dl), plasma sodium (134.6 ± 8.0mg/dl), plasma chloride (104.7± 4.0ng/dt) and plasma glucose (88.9 ± 33.6mM) recorded in semi-intensive system were the highest and were significantly different (P<0.05) from values obtained from the other culture systems. Haematological and hormonal balances of adult C. gariepinus were affected under short-term exposure to nitrite and ammonia toxicity in culture environment.